A Halophilic Bacterium for Bioremediation of Saline–Alkali Land: The Triadic and Synergetic Response Mechanism of Oceanobacillus picturae DY09 to Salt Stress - Tianying Nie; Liuqing Wang; Yilan Liu; Siqi Fu; Jiahui Wang; Kunpeng Cui; Lu Wang (Microorganisms, 2025)
The strain of Oceanobacillus picturae DY09, as a typical halophilic microorganism, possesses distinctive salt adaptation mechanisms that hold significant application value in the fields of agriculture, industry, and biomedicine. To deeply analyze the salt-tolerance molecular mechanism of this strain, this research disclosed its salt-tolerance strategies under diverse salt concentrations through transcriptomics. In a low-salt environment, the DY09 strain adopted a “metabolic simplification” strategy, significantly reducing the metabolic load by promoting lysine degradation and inhibiting the biosynthesis of branched-chain amino acids and glycine betaine (GB) but upregulating the expression of the GB transporter gene betH and preferentially utilizing exogenous GB to maintain basic osmotic balance. When exposed to high-salt stress, this strain activated multiple regulatory mechanisms: it upregulated the expression of Na+/K+ antiporter proteins to maintain ionic homeostasis; the synthesis genes of amino acids such as arginine and proline were significantly upregulated, and the GB synthesis genes betA/B and the transporter gene betH were upregulated concurrently, which realized the synergistic operation of endogenous synthesis and exogenous uptake of osmoprotective substances. The expression level of the antioxidant enzyme systems is upregulated to scavenge reactive oxygen species. Simultaneously, the molecular chaperones groES/groEL and GB cooperate to maintain the functional stability of the protein. In this study, a trinity salt-tolerance-integrated strategy of “dynamic perception–hierarchical response–system synergy” of halophilic bacteria was initially proposed, which provided a research idea for exploring the salt–alkali-tolerant mechanism of halophilic bacteria and a theoretical basis for the further development and application of this strain.